Hubungan Personal Hygiene Oleh Perawat Dengan Kepuasan Pasien Di Ruang Rawat Inap Rumah Sakit DR. R. Soeharsono Banjarmasin - Nurdiyah Fitriawati; Ahmad Juliadi; Didy Ariady (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2019)
Nurse service is an important aspect of health services to achieve patient satisfaction. One of the nurses' skills that can affect patient satisfaction is meeting the patient's personal hygiene needs. The purpose of the study was to determine the relationship of personal hygiene by nurses to the satisfaction of patients in the Inpatient Room of Dr. R. Soeharsono Banjarmasin. The study design was analytic descriptive with cross sectional approach. The population is all patients with physical immobility in the Inpatient Room of Dr. R. Soeharsono Banjarmasin as many as 89. Samples totaling 47 people with purposive sampling taking technique. Data analysis through the Spearman Rank test uses a confidence level of 95%. The results of the study showed that the personal hygeine patients by nurses were mostly less than 36 people (76.6%) and quite satisfied patients totaling 40 people (85.1%). There is a relationship between personal hygiene by nurses and patient satisfaction in the Inpatient Room of Dr. R. Soeharsono Banjarmasini (p value = 0.017